Converting Scientific Knowledge and Technical Innovation into Successful Business – Case of freshwater aquaculture - Barik, N K (Indian Farming, 2020)
The entrepreneurships were developed through wide range of services provided by ABI-CIFA. Incubatees were the primary focus of incubator with Incubatees (27) engaging in large number of enterprises in the freshwater aquaculture value chain. In addition, the entrepreneurs were also provided support through skill developments, mentoring and consultancy. During last 6 years, 79 entrepreneurs/firms were supported through 27 numbers of DPRs and entrepreneurs were able to attract funding to the tune of ` 26 crores and assets generated at about ` 34.2 crores. It is estimated that revenue generation by the entrepreneurs amounted to ` 13.72 crores per year. During this period 8 technologies were commercialised. Some of the brands like Tisya Pearls Pestolyset, Bindadd, fish Mount, Veggie Plus, freshterian etc. were developed by the entrepreneurs.